Respect of Human Rights and Freedoms During the Examination of a Person Within Criminal Proceedings: Issues of Theory and Practice - Yana Koniushenko; Nataliia Opanasenko; Anton Mariienko; Oleh Melnyk (Universidad Hemisferios, 2022)
Even though it becomes the responsibility of crime official to carry out the investigative phase so as to established commission, such procedure should be done by respecting the fundamental right of everyone. A person’s examination within criminal proceedings belongs to a range of investigative actions of restrictive nature. In this regard, the respect of human rights and freedoms becomes especially relevant during its conduction. According to experience in this field, law enforcement officers have questions on determining the subjects of this procedural action, the limits of applying coercion and the involvement of attesting witnesses. Systematic analysis of the Art. 241 of the Criminal Procedural Code of Ukraine demonstrated that the provisions set out in this Article are not sufficiently clear. That gives origins to the violations of human rights and freedoms. The authors have made a categorical conclusion about the need to improve the current regulations of the procedure for conducting examination within criminal proceedings. According to the results of the research, the authors have introduced scientifically sound proposals to improve the Ukrainian legislation concerning the procedure for conducting the investigation process.